Valorization of physicochemical properties of solid organic food waste for the preparation of composting - Pérez Pérez, Nelly Liliana (2023)
The management of organic solid waste is a global challenge, and they are experiencing growth commensurate with the population. This concern is due to the doubling of the production of organic solid waste, which is more than 1 billion tons per year. In order to minimize the generation of waste or reduce the volume of waste entering the sanitary landfill, it is suggested to use organic waste recycling as a circular economy strategy to produce biological composite materials. This study is a literature review of biological composite, aiming to determine the physical characteristics of physical and chemical parameters in the process of organic solid waste composting, to obtain various parameters affecting the process, such as pH value, water content, C/N ratio, temperature and particle size. According to the review, compost made from food residues provides more nutrition than agricultural and forestry wastes.